1999
DOI: 10.2331/fishsci.65.606
|View full text |Cite
|
Sign up to set email alerts
|

The Combined Effect of Transglutaminase and Protease Inhibitors on the Thermal Gelation of Actomyosin Sol from Carp and Salmon Muscles

Abstract: trans)carboxyoxran-2-carbonyl)-L-leucyl]agmatine (E64) was purchased from Peptide Institute. All other chemicals were of analytical grade from Wako Pure Chemical Indus tries. Microbial transglutaminase (MTGase, EC 2.3.2.13) was supplied by Ajinomoto Co. Inc. The specific activity was determined to be 260 unit/ mg by the method de scribed by Kishi et al.16) One unit of the activity was de fined as the amount of enzyme that catalyzed the incorpo ration of 1 nmol MDC into acetylated casein for 1 min of incubation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 30 publications
1
13
1
Order By: Relevance
“…All heated gels, however, showed similar low G′′ values. The overall profiles of the changes in G′ of adductor muscle paste as a function of temperature were quite different from those of fish actomyosin paste as reported elsewhere 8,17–20 . The temporal decrease in G′ value at 48°C was weaker than that of fish.…”
Section: Resultscontrasting
confidence: 73%
“…All heated gels, however, showed similar low G′′ values. The overall profiles of the changes in G′ of adductor muscle paste as a function of temperature were quite different from those of fish actomyosin paste as reported elsewhere 8,17–20 . The temporal decrease in G′ value at 48°C was weaker than that of fish.…”
Section: Resultscontrasting
confidence: 73%
“…7, because of a conformational state of actomyosin at a low pH. As reported in other studies, 16,21 the breaking strength of carp actomyosin gel increased with an increase in the activity level of added MTGase. The G″ value of actomyosin gel with MTGase decreased sharply after suwari and showed a small peak at approximately 65°C at pH 5.5 and 6.0 (Fig.…”
Section: Resultssupporting
confidence: 54%
“…A strong elastic gel was formed at pH 7.0 and 6.5 with a G′ value of 2500 Pa. Even at pH 6.0, a gel with a G′ value of 2000 Pa was formed and the suwari effect was more pronounced at 40°C than at 30°C 21 . Microbial TGase‐induced suwari was ineffective at pH 5.5.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The use of microbial transglutaminase is another possible means of improving gelation. Moreover, some studies have reported that protease inhibitors and microbial transglutaminase can be advantageously combined in fish species with poor gelforming ability [16].…”
Section: Introductionmentioning
confidence: 99%